IMPLEMENTASI PEMBERIAN NAFKAH IDDAH DI PENGADILAN AGAMA - Mohamad Hamim (Program Studi Hukum Keluarga Islam, 2022)
Iddah subsistence is a living that is given by the husband to his ex-wife because there hasbeen a regular divorce, this income is given because during this iddah the wife is still waitingfor the possibility of her ex-husband to return to her and the ex-wife is not allowed to marryanother man. The purpose of this study is to determine the concept of iddah living and thelegislation that is used as the basis for providing iddah living, to describe the implementationof iddah living in the Religious Courts and to analyze the arguments used by judges indeciding iddah living. This study uses a qualitative method by compiling the decisions of thereligious courts in Magelang, Kuningan and the City of Tasikmalaya. The results obtainedare 1) the iddah income given to the ex-wife is food, clothing and shelter. This livelihood isgiven if it is in the case of raj'i divorce and not because of the wife's nsuyusnya to herhusband. 2) the implementation of the provision of Iddah living in PA Magelang is obliged toprovide iddah support to the ex-wife even though with a verstek decision, in PA Kuningan thedivorce is still given because the wife is not proven to have committed nusysuz, the amount of